The power of the purse: gender, cooperation, and socially responsible consumption - Vásquez, Alejandra; Becchetti, Leonardo; Pelligra, Vittorio (Frontiers in Behavioral Economics, 2025)
We test for gender effects in the “vote with your wallet” game, a multi- person version of the prisoner's dilemma that models responsible consump- tion decisions. We find that women cooperate significantly more (have more responsible consumption decisions) than men in the baseline version of the game. This baseline excludes three additional elements tested in companion treatments: i) a legality frame, where the ethical product is labeled as being certified for compliance with anticorruption standards; ii) an ex-post redistribution scheme, where those who buy the less ethical product compensate those who choose the more responsible option; and iii) a conformity treatment, where participants are informed of prior players' choices to simulate social influence. Without these added interventions, women still show significantly greater cooperation, revealing a baseline preference for prosocial behavior in this strategic consumption setting.